(untitled) (Journal of the College of Basic Education, 2022)
The study represents an extensive presentation of a group of blind Arab Muslim scholars who had a distinguished impact in various scientific fields. He died in the year (712 AH / 1312 AD) without being registered in a city or in a scientific activity related to any of them, especially those whose achievements contributed to enriching several intellectual and scientific fields that prevailed in their society at the time. Although the concept of the blind does not mean that they are equal to their sighted peers; However, many of them had the opportunity to strive, relying on his sharp intelligence, and with the help of the Arab Islamic state, which was applying the teachings of Islam in caring for the blind, so that they rose to ascend the ranks of scholars and be among its men.